Análise experimental de parâmetros de combustão de um motor de injeção direta a etanol turbo-alimentado - Matheus Guilherme Franca Carvalho (2017)
The efficiency of internal combustion engines is directly related to the quality of the combustion and as a consequence to the engine-out emission and fuel consumption. One way to improve combustion efficiency is to inject the fuel directly into the combustion chamber, rather than injecting it into the intake manifold, as is done conventionally. Ethanol fuel due to its fuel properties such as high octane number and high charge cooling effect suppresses any knock occurrence at high loads operation, making possible to provide spark authority at low-end torque and consequently to produce high power at lower speeds (downspeeding) reducing significantly friction and pumping losses. With this, a substantial reduction in the size of the engines is possible, maintaining its performance by introducing a turbocharger set (downsizing). The integration of these technologies into a concept engine designed to maximize the ethanol combustion efficiency, enables similar fuel consumption results to larger displacement engines fueled with gasoline. From a downsized, supercharged engine, equipped with ethanol direct injection and CVCP system that allows overlap valves control, a study of the indicated combustion parameters is proposed, associating them with the fuel conversion efficiency for some operational conditions evaluated. The results analysis allowed to associate the influence of calibration parameters and engine geometric characteristics in the network produced, the heat generated and the combustion duration and stability. The fuel mixture stratification proved to be effective at high loads, allowing a 2% increase in fuel conversion efficiency. This knowledge is relevant for future research related to the ethanol combustion and its potential as an enabler of increasing overall engine efficiency and preserving the environment.